Household determinants of continued adoption of sustainable land management measures in central Ethiopia. Issue 3 (March 2023) - Alemu, Taye; Tolossa, Degefa; Senbeta, Feyera; Zeleke, Tesfaye
Abstract: The government of Ethiopia has undertaken several projects to restore degraded farmlands using a variety of sustainable land management (SLM) techniques. One of the critical elements of the program was the rehabilitation of farmlands using physical soil and water conservation (SWC) strategies. This study examines household determinants of continued SWC adoption performances using areas representing a variety of contexts. The analysis was conducted using a binary logit model based on data collected from 525 sample households in two districts, namely Kewet and Sebeta-hawas. Of the study participants, 276 households were from the Kewet district in the Amhara region, and 249 households were from Sebeta-hawas in the Oromia region. The study findings revealed a significant difference between sampled households in the study areas regarding continued adoption performances, i.e. (25%) in the Sebeta-hawas and (41%) in the Kewet districts. Among others, productivity gains, consistent follow-up, sufficient farm labor, livestock holding, assistance-free efforts, the experience of soil erosion risks, and sloppy farm plots provided incentives for households to embrace the already introduced measures. Aside from that, there appeared to be differences in the relative contributions and significance of determinants influencing the likelihood of continued adoption. The important conclusion is that adoption effectiveness may differ under different circumstances and agro-ecosystems. Variables influencing continued adoption are also context-specific. Thus, decision-makers should consider contextual variations in designing policies and strategies that promote adoption continuities and utilizations.